Vascular Anatomy in Congenital Lung Lesions—Description and Classification - Kargl, Simon; Schlader, Florian; Scala, Mario; Kammel, Julian (Frontiers in Pediatrics, 2022)
Background Bronchopulmonary sequestration (BPS) and hybrid lesion of congenital cystic adenomatoid malformation (CCAM) and BPS are congenital lung lesions typically presenting with systemic vascular connection. We describe and categorize this atypical systemic vascular anatomy in congenital lung lesions. Methods In a medical chart review from 2005 to 2020 patients with systemic vascular connection of congenital lung lesions were identified. Clinical and radiological data were collected and compared. Two experienced pediatric radiologists reviewed postnatal thoracic contrast-enhanced computed tomography scans to describe and categorize atypical vascular anatomy. We complete our findings with a review on vascular anatomy in congenital lung lesions. Results A total of 21 patients with congenital lung lesions (nine extralobar BPS, five intralobar BPS, seven hybrid lesions) had systemic arterial supply; with seven of these additionally having systemic venous drainage. Origin of the feeding arteries from the aorta or aortic main branches was described as supra-diaphragmatic (descending thoracic aorta) in nine and infra-diaphragmatic in ten patients (abdominal aorta, celiac trunk). In two patients with hybrid lesions both supra- and infra-diaphragmatic arterial feeders were found. Additional systemic venous connection of supra-diaphragmatic type drains into the azygos-hemiazygos system (4/21) while the infra-diaphragmatic type (3/21) drains into caval vein, portal or splenic vein. Conclusion Various variants of systemic arterial and venous connection of congenital lung lesions can be found. Classification of systemic arterial connection as well as venous drainage of congenital lung lesions as supra-diaphragmatic and infra-diaphragmatic types is intuitive, simple and may be important for the surgeon to avoid unanticipated situations and to perform safe resections.